MEDIA AND DEMOCRATIC GOVERNANCE IN NIGERIA - Abegunde, Ola; Fajimbola, Olatunde J. (International Journal of Research -GRANTHAALAYAH, 2018)
Democracy as a concept has become a common term among the generality of Nigerian citizens as a result of its frequent usage in the media. Although in the real sense of it, it has brought little dividends to Nigerians. In spite of its popular acceptance as the most favourable form of government in the world, the media in Nigeria has portrayed democracy in an uninspiring manner because of the greed, corruption and nepotism of Nigerian politicians thereby making the political communication of democracy as government of the people by the people and for the people unimpressive. Therefore, this paper examines the linkage between the media and democratic governance in Nigeria. It seeks to understand the ills that the media had caused to the democratic governance in Nigeria through sensational coverage of political events. The paper relied on secondary sources of data collection; and it is descriptive and explanatory in nature. The study anchored on Political Communication theory and Agenda-Setting theory to explain the influence of the media on democracy. The findings showed that Nigerian media is faced with myriads of challenges in fulfilling its duty as the watchdog of the society due to the issue of ownership, economic problem, and lack of adherence to professional ethics. It therefore recommended that adequate training that will reflect the ethics of the profession be given to media practitioners and other relevant stakeholders. Also, media practitioners including owners of medial houses should be exposed to an all-embracing political education that will enhance medial professionalism and appreciation of democratic values in Nigeria.